Disaggregated capital flows and economic growth: empirical evidences - Sarisae, Sufiana (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2011)
The main objective of this study is to examine the impacts of disaggregated capital flows, namely foreign direct investment (FDI) and equity foreign portfolio investment (EFPI) on economic growth in ASEAN-5 countries (Indonesia, Malaysia, Philippines, Singapore and Thailand), using panel data from the period 1987 to 2008. The purpose behind this study is to investigate whether financial development is the absorptive capacity that helps the host country to capture the capital inflows in order to harness real economic growth. The study also attempted to investigate how these two different types of flows (FDI & EFPI) have different impacts on economic growth of the ASEAN-5 countries. This study employs pooled OLS and fixed effects regression estimators. Overall, the empirical results suggest that FDI or EFPI alone has statistical insignificant impact on economic growth in ASEAN-5 countries. However, lagged FDI or lagged EFPI alone which is estimated together with lagged FDI or lagged EFPI based on interaction term- e.g. financial development-, respectively, has negative impact on economic growth. On the other hand, lagged FDI or lagged EFPI with interaction term- financial development- have a positive relationship with economic growth. Consequently, financial development is the key and important variable that helps the ASEAN-5 countries capture absorptive capacity to harness real economic growth. In addition, there is no much difference between the impact of FDI and EFPI on Economic growth. As result, the finding of this study will help policy makers to design elements for more stable and sociable global regulatory infrastructure, and also formulate policies in the liberalized world economy.